2018
DOI: 10.12659/ajcr.909278
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis Following Initiation of Antiviral Therapy with Oseltamivir

Abstract: Patient: Male, 53Final Diagnosis: Rhabdomyolysis with Oselatimivir therapySymptoms: Dark urineMedication: OseltamivirClinical Procedure: —Specialty: HematologyObjective:Adverse events of drug therapyBackground:Tamiflu (oseltamivir phosphate) serves as prophylaxis and treatment of upper respiratory tract infections (URTI) and lower respiratory tract infections (LRTI) caused by viruses of the Orthomyxovirus family. Here, we present a patient with URTI and negative rapid influenza diagnostic testing (RIDT), who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…He required vasopressors briefly on day 1 of his hospitalisation making sepsis an unlikely cause of the rhabdomyolysis. Oseltamivir has also been implicated as a rare aetiology of rhabdomyolysis 4–6. In our case, the patient presented with an elevated CK level of 3043 U/L at admission making it less likely the inciting event.…”
Section: Differential Diagnosismentioning
confidence: 72%
“…He required vasopressors briefly on day 1 of his hospitalisation making sepsis an unlikely cause of the rhabdomyolysis. Oseltamivir has also been implicated as a rare aetiology of rhabdomyolysis 4–6. In our case, the patient presented with an elevated CK level of 3043 U/L at admission making it less likely the inciting event.…”
Section: Differential Diagnosismentioning
confidence: 72%
“…In this case, the disease process and immune response against the influenza A (H3N2) virus may have induced the production of anti-SRP antibodies and worsened her myositis. Rhabdomyolysis caused by influenza virus itself or a drug (statin or oseltamivir (Puttagunta et al, 2018)) could be another differential diagnosis for the present case. However, renal dysfunction, which is usually correlated with a greater degree of rhabdomyolysis with severe muscular symptoms (Borgatta et al, 2012), was not observed in this patient; moreover, she did not respond to hydration treatment.…”
Section: Discussionmentioning
confidence: 86%